The Children's Gross Motor Ability Level (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2026)
Gross motor skills are fundamental components of children's physical development that support movement competence, physical activity participation, and readiness for learning, particularly during the elementary school years. Assessing children's gross motor abilities is essential to provide objective information that can be used to design appropriate physical education programs and developmental interventions. Therefore, this study aimed to determine the gross motor skill level of lower-grade students at SDI Alhidayah Palu using the Test of Gross Motor Development-2 (TGMD-2) instrument. This study employed a descriptive quantitative approach with a survey method. The population consisted of all lower-grade students at SDI Alhidayah Palu, totaling 30 children. Due to the relatively small population size, a total sampling technique was applied, involving all students as research participants. The TGMD-2 instrument was used to assess two major components of gross motor skills: locomotor skills and object-control skills. Data were analyzed using descriptive percentage statistics. The results revealed that in the locomotor skill component, 66.67% (20 students) were categorized as Good, 13.33% (4 students) as Very Good, 16.67% (5 students) as Moderate, and 3.33% (1 student) as Poor. In the object-control component, 60.00% (18 students) were categorized as Good, 6.67% (2 students) as Very Good, 23.33% (7 students) as Moderate, and 10.00% (3 students) as Poor. In conclusion, the overall gross motor skill level of lower-grade students at SDI Alhidayah Palu is classified as Good. Although students demonstrated satisfactory performance in both locomotor and object-control skills, additional stimulation and structured physical education activities, particularly focusing on object-control skills, are recommended to further optimize children's motor development.